Prevalence of Dental Fluorosis Among Adolescents in Schools of Greater Noida, Uttar Pradesh - Monica Chaudhry; Ishan Prabhakar; Bhuvandeep Gupta; Richa Anand; Priyanka Sehrawat; Sahil S Thakar (Wolters Kluwer Medknow Publications, 2017)
Introduction: Drinking water is one of the major sources of fluoride. India is one of those 24 countries where fluorosis is an important public health problem. When excess fluoride is ingested during the years of tooth calcification, it results in fluorosis. Aim: To assess the prevalence of dental fluorosis among adolescents in schools of Greater Noida, Uttar Pradesh. Materials and Methods: A total of 1318 students were examined for dental fluorosis through a stratified sampling technique from four blocks of Greater Noida. Dean's Fluorosis Index was used to record dental fluorosis and information regarding the source of water till the age of 8 years, usage of fluoridated toothpaste before 2 years of age and other affected family members, which was obtained from their parents. Results: The overall prevalence of dental fluorosis in Greater Noida was found to be 21.0%. A very mild form of dental fluorosis was seen in 27.6% of the adolescents. The source of water consumed by the adolescent till the age of 8 years was found to be significantly associated with dental fluorosis (P = 0.001). Adolescents who consumed water from the hand pump were more likely to develop dental fluorosis. The reporting of an affected family member was seen to vary significantly with the relative score of dental fluorosis observed for that adolescent. The value of Community Fluorosis Index (CFI) was found to be 1.7. Conclusion: Dental fluorosis seemed to be a problem of medium public health significance in Greater Noida as suggested by the observed CFI, which was 1.7. The consumption of water from the handpump by majority of the population was associated with fluorosis.